BAKTERI PATOGEN AEROB DAN UJI KEPEKAANNYA DI RUANGAN BEDAH PUSAT - Agustini Agustini; Nurhayana Sennang; Benny Rusli (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
An operating room is potential in causing nosocomial infection in a hospital, especially due to surgical wound infections. Nosocomialinfection raises the length of day care and disease transmission risk. According to Permenkes No. 1204/Menkes/SK/X/2004, the operatingroom is a highly infection risk area. The aim of this study is to know the determination of the amount of bacterial colonies count, andthe sensitivity identification pattern of pathogenic bacteria in the central operating rooms at the Dr Wahidin Sudirohusodo Hospital.A cross sectional study was done by taking air samples using a Microbiology Air Sampler 100 in six central operating rooms in Dr.Wahidin Sudirohusodo Hospital. Counting bacterial colonies, identifying pathogenic bacteria and sensitivity test were done at the BalaiBesar Laboratorium Kesehatan Makassar (from May to June 2010). The result of the study shows that the amount of bacterial coloniesfound were approximately 148–440 CFU/m3 aerobic pathogenic bacteria consisting of Alcaligenes faecalis and Serratia liquefacienswhich were sensitive to sulbactam+ cefoperazone, gentamycin, levofloxacin but resistant to ampicillin, nitrofurantoin, clindamycin andmetronidazole. The researchers concluded that the amount of bacterial colonies found exceeded the Permenkes standard. The pathogenicbacteria were sensitive to sulbactam+ cefoperazone, gentamycin and levofloxacin however, resistant to ampicillin, nitrofurantoin,clindamycin, and metronidazole.